A Study Regarding the Effects of Intercropping Celery with Cauliflower and Cherry Tomatoes - Florina Maria GALEA(DELEANU); Neculai MUNTEANU; Gabiel Ciprian TELIBAN; Silvia Brânduşa MAMBURDĂ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2017)
It has been proved that intercropping is a suitable approach for vegetable growing providing a high degree of sustainability. Due to its advantages this system reduces the presence of weeds, diseases and pests. Research was carried out in the experimental field of V. Adamachi farm from USAMV Iaşi. The biological material consist in three vegetable species: celery, cherry tomatoes and cauliflower and a flower, French marigold, cultivated in two intercropping systems, celery + cherry tomato + French marigold and celery + cauliflower. Biometric evaluations of celery plants were done on the edible part, length and width of the stalk and leaf, and number of leafs per plant. The obtained results showed in the two intercropping systems that celery plants were well developed, with a rich rosette and intense green colour of leaves. Celery, intercropped with cauliflower has a length and number of stalks slightly higher than the other system. The aim of this study is to analyze the agronomic and ornamental performances of the intercrop systems of celery with cauliflower and celery with tomatoes.